Discussion of Assessing Audit Risk from Errors and Irregularities - Watts, John S. (Journal of Accounting Research, 1990)
This paper uses the three-part model which identifies audit risk as IR CR . DR, where IR is the inherent risk that a material error or irregularity exists in an account, CR is the risk that the control system does not catch an error given that it exists, and DR is the risk that the auditor's procedures do not identify an error given that it exists and has been missed by the internal control system. The paper also takes as given that the auditor will use a hypothesis-testing framework for decision making. These assumptions are inspired by generally accepted auditing standards. As such, the paper takes an institutional setting as given and derives the behavior implied by the institution, rather than deriving an optimal institution. Analytically, the author's methods resemble those of Fellingham and Newman [1985] (hereafter FN) and Newman and Noel [1989] (hereafter NN).1 Similar to FN, the current paper shows how the equilibrium auditee strategies may be used to determine the analogue of the prior probability distribution used in decision-theoretic analyses of audit risk. Similar to NN, the author develops comparative statics on the equilibrium strategies with respect to auditor and auditee payoffs. A key feature distinguishing this paper from the other analyses is the addition of substantive testing to the audit setting; this allows the determination of DR in a strategic setting. Consequently, the three-part